Span of control and leadership satisfaction in public and private organizations - Bro, Louise Ladegaard; Langagergaard, Joachim; Jacobsen, Christian Bøtcher (Politica, 2019)
Public leaders are managing an increasing number of employees. The literature on span of control holds arguments about positive as well as negative effects of larger spans of control, but we lack empirical studies, which directly compare the consequences of span of control in public and private organizations. Furthermore, we lack panel studies, which investigate the consequences of changes in span of control. This article focuses on leadership satisfaction and investigates the importance of span of control among 11,234 public and private employees and shows that span of control is negatively associated with leadership satisfaction, and that this negative relationship is slightly stronger in public organizations compared with private organizations. Furthermore, a panel study of a subsample provides some support for the argument that changes in leadership satisfaction occur in relation to changes in span of control –especially at lower spans of control.